Injectable promethazine in clinics and hospitals: What's the alternative - Overholser, Andrew; Sizemore, Megan; Czech, Eric (JAAPA, 2025)
The Institute for Safe Medication Practices and the American Society of Health-System Pharmacists have advocated for removing all injectable promethazine from inpatient and outpatient settings; however, this drug is still being used despite the risk for tissue necrosis, gangrene, and possible amputation when it inadvertently is given by the subcutaneous or intra-arterial route. This article describes alternative injectable medications that can be selected based on patient comorbidities, indications, and clinician experience.
Keywords: promethazin; Promethazine; injekce; lidé; Injections; Injections, Subcutaneous; Humans; injekce subkutánní